Using Environmentally Friendly Media (Happy Body) in Early Childhood Science: Human Body Parts Lesson - suwahono, suwahono; Mawanti, Dwi (JURNAL PENDIDIKAN USIA DINI, 2019)
The knowledge of the science of human body parts for early childhood is very important so that children have the ability to recognize and support the cleanliness and health of members of the body, as well as so that they recognize their identity. In addition, introducing environmentally friendly material for early childhood teachers to enrich learning media. This study aims to improve student learning outcomes in science using environmentally friendly media. The topic raised in this search was about recognizing body parts and their benefits and treatments. This type of research is action research. Respondents involved 19 early childhood students. The results showed that there was an increase in subjects' understanding of swallowing extremities and treatment 60% in the pre-cycle phase, 80% in the first cycle and 93% in the second cycle. The findings show that the use of happy body media has a positive effect on limb recognition. Further research is recommended on environmentally friendly media and ways of introducing limbs to early childhood through media or strategies suitable for the millennial era. Keywords: Media (Happy Body), Early Childhood Science, Human Body Parts References: Anagnou, E., & Fragoulis, I. (2014). The contribution of mentoring and action research to teachers’ professional development in the context of informal learning. Review of European Studies, 6(1), 133–142. Belsky, J., Steinberg, L., & Draper, P. (1991). Childhood experience, interpersonal development, and reproductive strategy: An evolutionary theory of socialization. Child Development, 62(4), 647. Black, M. M., & Hurley, K. M. (2016). Early child development programmes: further evidence for action. The Lancet Global Health, 4(8), e505–e506. Blok, H., Fukkink, R., Gebhardt, E., & Leseman, P. (2005). The relevance of delivery mode and other programme characteristics for the effectiveness of early childhood intervention. International Journal of Behavioral Development, 29(1), 35–47. Borg, F., Winberg, M., & Vinterek, M. (2017). Children’s Learning for a Sustainable Society: Influences from Home and Preschool. Education Inquiry, 8(2), 151–172. https://doi.org/10.1080/20004508.2017.1290915 Borg, F., Winberg, T. M., & Vinterek, M. (2019). Preschool children’s knowledge about the environmental impact of various modes of transport. Early Child Development and Care, 189(3), 376–391. https://doi.org/10.1080/03004430.2017.1324433 Buchsbaum, D., Bridgers, S., Weisberg, D. S., &, & Gopnik, A. (2012). The power of possibility: Causal learning, counterfactual reasoning, and pretend play. Philosophical Transactions of the Royal Society. Biological Sciences, 367(1599), 2202–2212. Burdette, H. L., & Whitaker, R. C. (2005). Resurrecting free play in young children: looking beyond fitness and fatness to attention, affiliation, and affect. Archives of Pediatrics & Adolescent Medicine, 159(1), 46–50. Bustamante, A. S., White, L. J., & Greenfield, D. B. (2018). Approaches to learning and science education in Head Start: Examining bidirectionality. Early Childhood Research Quarterly, 44, 34–42. https://doi.org/10.1016/j.ecresq.2018.02.013 Carr, W. (2006). Philosophy, methodology and action research. Journal of Philosophy of Education, 40(4), 421–435. Colker, L. J. (2008). Twelve characteristics of effective early childhood teachers. YC Young Children, 63(2). Cook, C., Goodman, N. D., & Schulz, L. E. (2011). Where science starts: Spontaneous experiments in preschoolers’ exploratory play. Cognition, 120(3), 341– 349. Dewi Kurnia, H. Z. (2017). Pentingnya Media Pembelajaran. Jurnal Pendidikan Anak Usia Dini, 1 No.1, 81–96. Gelman, R., & Brenneman, K. (2004). Science learning pathways for young children. Early Childhood Research Quarterly, 19(1), 150–158. Gersick, C. J. (1988). Time and transition in work teams: Toward a new model of group development. Academy of Management Journal, 31(1), 9–41. Gopnik, A., Meltzoﬀ, A. N., & Kuhl, P. K. (1999). The scientist in the crib: Mind, brains, and how children learn. New York, NY: William Morrow & Company. Guo, Y., Wang, S., Hall, A. H., Breit-Smith, A., & Busch, J. (2016). The Effects of Science Instruction on Young Children’s Vocabulary Learning: A Research Synthesis. Early Childhood Education Journal, 44(4), 359–367. https://doi.org/10.1007/s10643-015-0721-6 Hadders-Algra, M. (2019). Interactive media use and early childhood development. Jornal de Pediatria, (xx), 1–3. https://doi.org/10.1016/j.jped.2019.05.001 Han, S., Capraro, R., & Capraro, M. M. (2015). How Science, Technology, Engineering, and Mathematics (Stem) Project-Based Learning (Pbl) Affects High, Middle, and Low Achievers Differently: the Impact of Student Factors on Achievement. International Journal of Science and Mathematics Education, 13(5), 1089–1113. https://doi.org/10.1007/s10763-014-9526-0 Harris, P. L., & Kavanaugh, R. D. (1993). Young children’s understanding of pretense. Monographs of the Society for Research in Child Development, 58(1), 1–92. Hayati, H. S., Myrnawati, C. H., & Asmawi, M. (2017). Effect of Traditional Games, Learning Motivation And Learning Style On Childhoods Gross Motor Skills. International Journal of Education and Research, 5(7). Hedefalk, M., Almqvist, J., & Östman, L. (2015). Education for sustainable development in early childhood education: a review of the research literature. Environmental Education Research, 21(7), 975–990. https://doi.org/10.1080/13504622.2014.971716 Herakleioti, E., & Pantidos, P. (2016). The Contribution of the Human Body in Young Children’s Explanations About Shadow Formation. Research in Science Education, 46(1), 21–42. https://doi.org/10.1007/s11165-014-9458-2 İlin, G., Kutlu, Ö., & Kutluay, A. (2013). An Action Research: Using Videos for Teaching Grammar in an ESP Class. Procedia - Social and Behavioral Sciences. https://doi.org/https://doi.org/10.1016/j.sbspro.2013.01.065 Jennifer M. Zosh, Emily J. Hopkins, Hanne Jensen, Claire Liu, Dave Neale, Kathy Hirsh-Pasek, S. L. S. and D. W. (2017). Learning through play : a review of the evidence. Kagan, J., Reznick, J. S., & Snidman, N. (1987). The physiology and psychology of behavioral inhibition in children. Child Development, 1459–1473. Kemmis, S., & Taggart, M. (2002). The action research planner. Victoria: Dearcin University Press. Lebel, C., & Beaulieu, C. (2011). Longitudinal development of human brain wiring continues from childhood into adulthood. Journal of Neuroscience, 31(30), 10937–10947. Luna, B., Garver, K. E., Urban, T. A., Lazar, N. A., & Sweeney, J. A. (2004). Maturation of cognitive processes from late childhood to adulthood. Child Development, 75(5), 1357–1372. Nayfeld, I., Brenneman, K., & Gelman, R. (2011). Science in the classroom: Finding a balance between autonomous exploration and teacher-led instruction in preschool settings. Early Education & Development, 22(6), 970–988. Nitecki, E., & Chung, M.-H. (2016). Play as Place: A Safe Space for Young Children to Learn about the World. Nternational Journal of Early Childhood Environmental Education, 4(1), 26–32. Olgan, R. (2015). Influences on Turkish early childhood teachers’ science teaching practices and the science content covered in the early years. Early Child Development and Care, 185(6), 926-942. Ramani, G. B. (2012). Inﬂuence of a Playful, Child-Directed Context on Preschool Children’s Peer Cooperation. New York: Merrill-Palmer Quarterly. Ravanis, K. (2017). Early childhood science education: State of the art and perspectives. Journal of Baltic Science Education, 16(3), 284–288. Russo-Johnson C, Troseth G, Duncan C, M. A. (2017). All tapped out: touchscreen interactivity and young children’s word learning. Front Psychology, 8. Schulz, L. E., & Bonawitz, E. B. (2007). Serious fun: Preschoolers engage in more exploratory play when evidence is confounde. Developmental Psycholog, 43(4), 1045–1050. Serpell, R., & Marfo, K. (2014). Some growth points in African child development research. New Directions for Child and Adolescent Development, 146, 97–112. Vouloumanos, A., & Werker, J. F. (2007). Listening to language at birth: evidence for a bias for speech in neonates. Developmental Science, 10(2), 59–64. Weisberg, D. S., & Gopnik, A. (2013). Pretense, counterfactuals, and Bayesian causal models: Why what is not real really matters. Cognitive Science, 37(7), 1368–1381. Winthrop, R., & Mcgivney, E. (2016). Skills for a Changing World: Advancing Quality Learning for Vibrant Societies.Brookings: Center for Universal Education. Zaman, B., & Eliyawati, C. (2010). Media Pembelajaran Anak Usia Dini. Bandung: Universitas Pendidikan Indonesia.